The importance of breastfeeding in preventing food allergies (Research, Society and Development, 2022)
Introduction: Food allergies are diseases resulting from immune responses that have symptoms that affect both the health and lifestyle of individuals. Its causes are possibly linked to genetic factors and environmental exposure. Objectives General: to evaluate the consequences for the child's health as a result of early weaning and the relationship with food allergies. Methodology: The Methodological procedures were carried out through bibliographic research, in this way, it was sought in the literature, in articles, books and reference sites that made possible theoretical knowledge of the research theme. Results and Discussion: The superiority of Breastfeeding over other ways of feeding young children is scientifically proven, but most Brazilian children are not breastfed for two years or more, and do not receive exclusive breast milk in the first six months of life. Conclusion: From this study it was possible to discuss the risks and harms of an early food introduction and to show that before six months nothing replaces breast milk, since it is complete containing all the necessary elements for the healthy development of the child, and that is why it is very important that mothers prioritize it until six months of age, in order to avoid the emergence of allergies and other possible complications.